ANALISA PENGARUH FAKTOR-FAKTOR PEMBENTUK FEE IJARAH (PSAK 107) TERHADAP PORTOFOLIO RAHN EMAS DI BANK SYARIAH - ., Yanti (Program Studi Akuntansi, 2018)
ABSTRACT This study aims to explain the influence of the factors forming the portfolio Rahn Ijarah fee at Bank Syariah gold as an Islamic Financial Institutions that have a product based on Ijarah, and to analyze the compliance by the prevailing regulations in Indonesia, the DSN-MUI Fatwa No.27 / DSN- MUI / III / 2002 and PSAK 107,